2010
DOI: 10.3945/ajcn.2010.29345
|View full text |Cite
|
Sign up to set email alerts
|

Mediterranean and carbohydrate-restricted diets and mortality among elderly men: a cohort study in Sweden

Abstract: Adherence to a Mediterranean-like dietary pattern reduced mortality, whereas adherence to a CR dietary pattern appeared to increase mortality in elderly Swedish men, especially when only adequate dietary reporters were considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
122
2
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(136 citation statements)
references
References 26 publications
9
122
2
3
Order By: Relevance
“…9,10 Saturated fat was the most important confounder in our study. However, other studies have reported a positive association between a carbohydrate-restricted diet and increased mortality after adjusting for saturated fat, 11 or with fat intake taken into account by other means.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…9,10 Saturated fat was the most important confounder in our study. However, other studies have reported a positive association between a carbohydrate-restricted diet and increased mortality after adjusting for saturated fat, 11 or with fat intake taken into account by other means.…”
Section: Discussionmentioning
confidence: 87%
“…9,11,12 In one study, an increased mortality at high LCHP scores was found in subjects with coronary artery disease and diabetes. 10 The reduced CVD mortality at high LCHP scores in men with diabetes in our study is thus a novel finding.…”
Section: Discussionmentioning
confidence: 99%
“…The updated search from recent years resulted in the identification of eighteen additional prospective studies published up to June 2013 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) . Characteristics of these recent studies are displayed in Table 3.…”
Section: Updated Systematic Review and Meta-analysismentioning
confidence: 99%
“…Characteristics of these recent studies are displayed in Table 3. Of these, seven cohorts presented overall mortality as clinical outcome (7,8,10,11,(14)(15)(16) , eight incidence and/or mortality from cardio-and cerebrovascular diseases (7,9,10,12,(16)(17)(18)(19) , and eight incidence and/or mortality from neoplastic diseases (10,13,16,(20)(21)(22)(23)(24) . No updated studies for the incidence of neurodegenerative diseases have been found.…”
Section: Updated Systematic Review and Meta-analysismentioning
confidence: 99%
“…14 Such benefits have been observed both in Mediterranean 15 as well as in non-Mediterranean countries. 16 Adherence to a Mediterranean-like dietary pattern has often been evaluated based on scores. The most commonly applied Mediterranean diet score (MDS) used in studies on adults was developed by Trichopoulou et al 17 The score was subsequently modified to include fish 18,19 or calculated based on tertile rather than median intakes for application in large population studies.…”
Section: Introductionmentioning
confidence: 99%